Looking Backwards into a Mediterranean Edge Environment: Landscape Changes in El Congost Valley (Catalonia), 1850-2005. (1st August 2014) - Tello, Enric; Valldeperas, Natàlia; Ollés, Anna; Marull, Joan; Coll, Francesc; Warde, Paul; Wilcox, Paul Thomas
Abstract : We examine the evolution from the mid-nineteenth century to the present of the cultural landscape in two Catalan townships that jointly constitute an edge environment between Mediterranean plain and mountain. This environmental edge has changed over time, from a border between an agricultural plain confronting an area of forestry and livestock-raising in the mid-nineteenth century, to a limit of the Barcelona Metropolitan Region confronting two 'natural' protected sites in the present. Over a century and a half land use changes in this area have brought about the two main, but superficially 'opposed' dynamics that characterise landscape evolution throughout Catalonia and great parts of Europe today: intensification and abandonment. The most salient ecological impact of both processes has been the loss of landscape mosaics. In the plain those mosaics interwove cereal cropping with vineyards and olive orchards together with patches of woodland, scrubland and pastureland into an agricultural land matrix. In the mountains, a woodland matrix of holm oaks and pines became cleared through timber and firewood extraction, and the pruning of branches for charcoal making, creating a mixture of open forest articulated by grazing areas, cropland and scrub. Both sides of the edge interlinked, and jointly played a key role as ecological connectors to maintain biodiversity. From the 1960s onwards the ecological dynamics attendant upon the abandonment of the prevailing integrated management of forests, livestock breeding and cropland has led to a significant loss of these landscape mosaics. In spite of the transformation of much of this area into natural protected sites, the growth of a uniform and continuous reforested woodland canopy, directly confronted with urban sprawl, is endangering its richness in terms of species - such as Mediterranean orchids, whose habitats are disappearing.